On the stability of KdV equation with time-dependent delay on the boundary feedback in presence of saturated source term - ENNOUARI, Toufik; TABOYE, Ahmat Mahamat (Studia Universitatis Babeș-Bolyai Mathematica, 2025)
The current paper investigate the question of stabilizability of the Korteweg-de Vries equation with time-varying delay on the boundary feedback in the presence of a saturated source term. Under specific assumptions regarding the time-varying delay, we have established that the studied system is well-posed. Moreover, using an appropriate Lyapunov functional, we prove the exponential stability result. Finally, we give some conclusions. Mathematics Subject Classification (2010): 93B05, 35R02, 93C20. Received 30 March 2024; Accepted 22 May 2024.